The Impairment of Macrophage-to-Feces Reverse Cholesterol Transport during Inflammation Does Not Depend on Serum Amyloid A. (30th January 2013) - de Beer, Maria C.; Wroblewski, Joanne M.; Noffsinger, Victoria P.; Ji, Ailing; Meyer, Jason M.; van der Westhuyzen, Deneys R.; de Beer, Frederick C.; Webb, Nancy R.
Abstract : Studies suggest that inflammation impairs reverse cholesterol transport (RCT). We investigated whether serum amyloid A (SAA) contributes to this impairment using an established macrophage-to-feces RCT model. Wild-type (WT) mice and mice deficient in SAA1.1 and SAA2.1 (SAAKO) were injected intraperitoneally with 3 H-cholesterol-labeled J774 macrophages 4 hr after administration of LPS or buffered saline. 3 H-cholesterol in plasma 4 hr after macrophage injection was significantly reduced in both WT and SAAKO mice injected with LPS, but this was not associated with a reduced capacity of serum from LPS-injected mice to promote macrophage cholesterol efflux in vitro . Hepatic accumulation of 3 H-cholesterol was unaltered in either WT or SAAKO mice by LPS treatment. Radioactivity present in bile and feces of LPS-injected WT mice 24 hr after macrophage injection was reduced by 36%   ( P < 0.05 ) and 80%   ( P < 0.001 ), respectively. In contrast, in SAAKO mice, LPS did not significantly reduce macrophage-derived 3 H-cholesterol in bile, and fecal excretion was reduced by only 45%   ( P < 0.05 ) . Injection of cholesterol-loaded allogeneic J774 cells, but not syngeneic bone-marrow-derived macrophages, transiently induced SAA in C57BL/6 mice. Our study confirms reports that acute inflammation impairs steps in the RCT pathway and establishes that SAA plays only a minor role in this impairment.